2021
DOI: 10.1038/s41598-021-00281-y
|View full text |Cite
|
Sign up to set email alerts
|

Spatial representability of neuronal activity

Abstract: A common approach to interpreting spiking activity is based on identifying the firing fields—regions in physical or configuration spaces that elicit responses of neurons. Common examples include hippocampal place cells that fire at preferred locations in the navigated environment, head direction cells that fire at preferred orientations of the animal’s head, view cells that respond to preferred spots in the visual field, etc. In all these cases, firing fields were discovered empirically, by trial and error. We… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 113 publications
0
1
0
Order By: Relevance
“…In previous studies, persistent cohomology has found a ring-shaped data structure of H 0 = 1, H 1 = 1, H 2 = 0 in the population activity of place cells and head orientation cells [10] [11] [12] [13] [14]. In particular, in the case of head direction cells, the animal’s head direction can be estimated from 0 to the 360-degree phase of the ring-shaped data structure.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, persistent cohomology has found a ring-shaped data structure of H 0 = 1, H 1 = 1, H 2 = 0 in the population activity of place cells and head orientation cells [10] [11] [12] [13] [14]. In particular, in the case of head direction cells, the animal’s head direction can be estimated from 0 to the 360-degree phase of the ring-shaped data structure.…”
Section: Introductionmentioning
confidence: 99%